Evaluation of NTP42, a novel thromboxane receptor antagonist, in a first-in-human phase I clinical trial - Reid, Helen M.; Maginn, Mark; Perkins, C. Michael; Mulvaney, Eamon P.; Boyce, Malcolm; Yamamoto, Takahiro; Kinsella, B. Therese (Frontiers in Pharmacology, 2023)
Background: The thromboxane receptor (TP) antagonist NTP42 is in clinical development for treatment of cardiopulmonary diseases, such as pulmonary arterial hypertension. In this randomized, placebo-controlled Phase I clinical trial, NTP42, administered as the oral formulation NTP42:KVA4, was evaluated for safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) in healthy males. Methods: The first-in-human trial had three Parts: A, single ascending dose (SAD) study with 7 groups given 0.25–243 mg NTP42:KVA4 or placebo; B, food effect study where one SAD group (9 mg) was also given NTP42:KVA4 or placebo after a high-fat breakfast; C, multiple ascending dose study with 3 groups given 15–135 mg NTP42:KVA4 or placebo once-daily for seven days. Results: Seventy-nine volunteers participated. No serious adverse events occurred, where any drug- or placebo-related adverse events were mild to moderate, with no correlation to NTP42:KVA4 dose. NTP42 was rapidly absorbed, yielding dose proportional increases in exposure after single and repeat dosing. PK confirmed that, with a clearance (T1/2) of 18.7 h, NTP42:KVA4 is suited to once-daily dosing, can be taken with or without food, and does not accumulate on repeat dosing. At doses ≥ 1 mg, NTP42 led to complete and sustained inhibition of thromboxane-, but not ADP-, induced platelet aggregation ex vivo, with direct correlation between NTP42 exposure and duration of PD effects. Conclusions: Orally administered NTP42:KVA4 was well tolerated, with favorable PK/PD profiles and evidence of specific TP target engagement. These findings support continued clinical development of NTP42:KVA4 for cardiopulmonary or other relevant diseases with unmet needs.